2018
DOI: 10.1016/j.apsb.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the modulation of sirtuins on arylamine N-acetyltransferase 1 and 2 enzymatic activity

Abstract: Arylamine N-acetyltransferase (NAT; E.C. 2.3.1.5) enzymes are responsible for the biotransformation of several arylamine and hydrazine drugs by acetylation. In this process, the acetyl group transferred to the acceptor substrate produces NAT deacetylation and, in consequence, it is susceptible of degradation. Sirtuins are protein deacetylases, dependent on nicotine adenine dinucleotide, which perform post-translational modifications on cytosolic proteins. To explore possible sirtuin participation in the enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…After treated with the compounds for the indicated times, cells were lysed by RIPA buffer (150 mmol/L NaCl, 1% NP-40, 0.5% sodium deoxycholate, 0.1% SDS, 50 mmol/L Tris-HCl, pH 7.5) containing protease and phosphatase inhibitor cocktail (Merck Millipore, Billerica, MA, USA) with freshly added 1 mmol/L of PMSF. After centrifugation at 12,000 rpm (MicroCL 17R, Thermo Fisher Scientific, Waltham, MA, USA) at 4 °C for 20 min, supernatants were collected and equal amounts of protein were subjected to Western blot assay as described before37, 38. After being visualized using an electrochemiluminescence kit (Sudgen, China), luminescence was assessed by chemiluminescent imaging system (Tanon, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…After treated with the compounds for the indicated times, cells were lysed by RIPA buffer (150 mmol/L NaCl, 1% NP-40, 0.5% sodium deoxycholate, 0.1% SDS, 50 mmol/L Tris-HCl, pH 7.5) containing protease and phosphatase inhibitor cocktail (Merck Millipore, Billerica, MA, USA) with freshly added 1 mmol/L of PMSF. After centrifugation at 12,000 rpm (MicroCL 17R, Thermo Fisher Scientific, Waltham, MA, USA) at 4 °C for 20 min, supernatants were collected and equal amounts of protein were subjected to Western blot assay as described before37, 38. After being visualized using an electrochemiluminescence kit (Sudgen, China), luminescence was assessed by chemiluminescent imaging system (Tanon, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism behind this phenomenon is H3K56 acetylation [36]. Using HeLa cells as positive control researchers found that once deacetylation function of sirtuins was suppressed, they were impossible to remove the acetyl groups from arylamine N -acetyltransferase 2 (NAT2), making this protein more stable, thereby increasing the activity of NAT2 [37]. The acetylation of P53 increased in Sirt1 silenced HeLa cells.…”
Section: Histone Deacetylasesmentioning
confidence: 99%
“…A regulation mechanism proposed for N-acetyltransferase 1 suggests a role for acetylation/deacetylation equilibrium that confers stability to the protein and prevents lysine deacetylation and ubiquitin degradation [23]. A recent report provided preliminary data in support of Sirtuin modulation of NAT2 [24]. …”
Section: Introductionmentioning
confidence: 99%
“…NAT2 and SIRT1 expression were evaluated on PBMC using different combinations of monoclonal antibodies on the T, B or NK cell subpopulations as previously reported [24, 33, 34]. Briefly, to detect CD3, CD19 or CD56 molecules on plasmatic membrane an incubation step using the corresponding monoclonal antibodies, anti-CD3-PE, anti-CD19-PE or anti-CD56-PE was performed (BD Biosciences, San Jose, CA, USA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation